Symbolic Extensions of Amenable Group Actions and the Comparison Property - Downarowicz, Tomasz; Zhang, Guohua (Memoirs of the American Mathematical Society, 2023)
In topological dynamics, the Of course, the statement is preceded by the presentation of the concepts of an entropy structure and its superenvelopes, adapted from the case of